(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
Autoficcional dramaturgy created from experimental exercises of the authors in their search for the intertwining between body and writing. Linked to research projects Education and Arts of the Body: other presences for other times and The theatrical discourse: dialogical resonances on screen (CNPq Support), this text is configured as a proposition that explores and raises articulations with different verbal, visual and verbal-visual dimensions, while mobilizing the notion of theatrical discourse seeking to investigate the functioning of its discursive resonances in contemporaneity.